139k views
5 votes
Help please, it’s for average rate of change.

Help please, it’s for average rate of change.-example-1
User Bernte
by
5.9k points

1 Answer

3 votes

Answer in fraction form = -3/2

Answer in decimal form = -1.5

=========================================

Work Shown:


m = (g(b)-g(a))/(b-a)\\\\m = (g(1)-g(-3))/(1-(-3))\\\\m = (0-6)/(1-(-3))\\\\m = (0-6)/(1+3)\\\\m = (-6)/(4)\\\\m = -(3)/(2)\\\\m = -1.5\\\\

Effectively, we're finding the slope through the points (-3, 6) and (1, 0)

The g(b)-g(a) represents how y changes when going from x = a to x = b.

User Youbetternot
by
6.3k points